PELESTARIAN BAHASA, AKSARA, DAN SASTRA BALI MELALUI PENGOPTIMALAN TRIPUSAT PENDIDIKAN - I MADE ARIASA GIRI (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
The existence of language, akasara, and literature Bali has a position and a very important function, namely as a pillar of the nation's cultural development. Along with the development of globalization, its presence is experiencing a dynamic, such as the decrease in the use of language Bali in quantity and quality. It is increasingly threatening kelestraiannya, whereas language, literacy and regional literature has an important role in building character or national identity. Therefore, it is important to efforts to preserve the language, script and literature tripusat Bali through optimization of education, the family environment, school, and community. Family environment is an environment is first and foremost for a child. The school environment is a second environment for children to socialize and interact. Community environment is also very important take on the role especially Pakraman and community leaders. In the preservation of language, literacy, and literary Bali can not be separated from a variety of challenges.